Decision support for the planning of integrated wastewater reuse projects in South Africa - Adewumi, J. R.; Ilemobade, A. A.; van Zyl, J. E. (Water science & technology. Water supply, 2010)
Wastewater reuse is an attractive option for supplementing available water supplies. Benefits of reuse include pollution abatement due to the reduction of effluent discharge to surface water bodies, the decrease in the use of freshwaters from sensitive ecosystems, replenishment of soil nutrients in agriculture, enhancement of groundwater recharge and delay in the future expansion of water supply infrastructure. This paper presents ongoing research in developing and testing of a decision support system (DSS) for assessing the feasibility of implementing wastewater reuse projects in South Africa. The DSS employs multi-criteria qualitative assessment across technical, environmental, social, institution and water resources. The database of the DSS contains 33 wastewater treatment unit processes with known information on performance, costs and qualitative criteria obtained from literature. The knowledge base on the other hand, consists of a set of rules for combining the treatment units to form treatment trains and contains information on maximum allowable values for different water quality parameters for five end users. The weighted average method was used to aggregate scores obtained from the assessment of the different criteria to generate an indicative value that could form the basis for decision making. Testing of the DSS was applied to the Parow wastewater treatment plant in Cape Town. Results of the analysis shows that only the water resources evaluation score (1.0) is considered excellent for reuse implementation while the institutional evaluation score is weak (0.35) in guaranteeing success. Social evaluation and treatment train technical/environmental have qualitative evaluation scores of 0.76. The desirable score for all the criteria is 1.0 in order to facilitate the successful implementation of any reuse project. The quality of treated effluent from the proposed treatment trains meets the quality requirement in most of the pollutant determined except total phosphorus (2.88). The value is acceptable if the use of the effluent is limited to irrigation. If decision makers give adequate attention to the criteria highlighted in this model, success of a reuse project in South Africa can be better enhanced.